The impact of an ICME on the Jovian X‐ray aurora. Issue 3 (22nd March 2016) - Dunn, William R.; Branduardi‐Raymont, Graziella; Elsner, Ronald F.; Vogt, Marissa F.; Lamy, Laurent; Ford, Peter G.; Coates, Andrew J.; Gladstone, G. Randall; Jackman, Caitriona M.; Nichols, Jonathan D.; Rae, I. Jonathan; Varsani, Ali; et al.
Abstract: We report the first Jupiter X‐ray observations planned to coincide with an interplanetary coronal mass ejection (ICME). At the predicted ICME arrival time, we observed a factor of ∼8 enhancement in Jupiter's X‐ray aurora. Within 1.5 h of this enhancement, intense bursts of non‐Io decametric radio emission occurred. Spatial, spectral, and temporal characteristics also varied between ICME arrival and another X‐ray observation two days later. Gladstone et al. (2002) discovered the polar X‐ray hot spot and found it pulsed with 45 min quasiperiodicity. During the ICME arrival, the hot spot expanded and exhibited two periods: 26 min periodicity from sulfur ions and 12 min periodicity from a mixture of carbon/sulfur and oxygen ions. After the ICME, the dominant period became 42 min. By comparing Vogt et al. (2011) Jovian mapping models with spectral analysis, we found that during ICME arrival at least two distinct ion populations, from Jupiter's dayside, produced the X‐ray aurora. Auroras mapping to magnetospheric field lines between 50 and 70 R J were dominated by emission from precipitating sulfur ions (S 7+, …, 14+ ). Emissions mapping to closed field lines between 70 and 120 R J and to open field lines were generated by a mixture of precipitating oxygen (O 7+, 8+ ) and sulfur/carbon ions, possibly implying some solar wind precipitation. We suggest that the best explanation for the X‐ray hot spot is pulsed dayside reconnection perturbing magnetospheric downward currents, as proposed by Bunce et al. (2004). The auroral enhancement has different spectral, spatial, and temporal characteristics to the hot spot. By analyzing these characteristics and coincident radio emissions, we propose that the enhancement is driven directly by the ICME through Jovian magnetosphere compression and/or a large‐scale dayside reconnection event. Key Points: The arrival of an ICME changes Jupiter's X‐ray auroral spectra, spatial, and temporal characteristics Jupiter's X‐ray aurora maps to sources in the outer magnetosphere and also to open field lines Jupiter's X‐ray aurora is produced by two distinct ion populations during the ICME